Transforming Patient Care: A Systematic Review of the Impact of eHealth on Healthcare Delivery - Al Zulayq, Alhassan Ali Salem; Al-Zulaiq, Saleh Ali Salem; ALKhomsan, Salem Mohammed Saleh; Al khamsan, Salem Nasser Mohammed; Al khamsan, Nasser Saleh Mesfer; alsuliman, Ali Mohd Hassan; Almahamed, Bader Ali Saleh; Alkhamsan, Hamad Mohamed Yahya; Al sulaiman, Hassein Ali Alban; Alhadhban, Sarra Moaid; Almodhaibri, Saleh Salamah Homood (Journal of Ecohumanism, 2024)
eHealth technologies have emerged as transformative tools in modern healthcare, offering solutions to improve patient care delivery by enhancing accessibility, efficiency, and quality. This systematic review examines the impact of eHealth on healthcare delivery, focusing on telemedicine, electronic health records, and mobile health applications. A total of X studies were analyzed, highlighting significant improvements in diagnostic accuracy, treatment personalization, and patient satisfaction, particularly in underserved areas. However, challenges such as technological barriers, data privacy concerns, and resistance to adoption persist. The findings underscore the potential of eHealth to revolutionize healthcare delivery while emphasizing the need for policies and frameworks to address existing challenges and ensure equitable implementation.